Superoxide Dismutase (MnSOD) Gene Polymorphism in Workers Exposed to Heavy Metals in Some of Industrial Foundations - Jalood, Hayder Hussein; Al-Rekaby, Hassan R.; Maktoof, Afrah Abid (International Journal of Psychosocial Rehabilitation, 2020)
The current study was aimed to study the concentrations of (Pb, Cd, Fe, Cu and Zn) workers exposed to heavy metals in some of industrial foundations with various genotypes of MnSOD Val16Ala polymorphism. It was also aimed to detection the mutation in MnSOD gene. The concentrations of Pb, Cd, Fe, Cu and Zn was analyzed by Atomic absorption spectrophotometer. DNA was extracted and MnSOD genes was amplification by polymerase chain reaction (PCR). PCR products sent to a Macrogen Company to sequencing. There was a significant difference between ion metals concentration in the serum of workers and control. The current study showed a significant differences between TC genotype and TT genotype as a reference allele in the control and oil refinery workers group (OR 1.62, 95% CI 0.36 – 7.20). In workers of brick factories, the risk ratio increased with TC genotype (OR 1.73, 95% CI 0.31 – 9.57), while the risk ratio increased by approximately two and a half times in the workers with the CC genotype (OR 2.60, 95% CI 0.51 – 13.04). The current study recorded 11 mutation in different locus of target sequence. The most common mutation was the insertion of G base at locus 74857 of the gene, which may be effect of synthesis protein at this gene locus to the end of protein. This study concluded that the majority of workers carry allele T, which is associated with diseases-related of oxidative stress. Exposure of workers with TT genotype to heavy metals is a risk factor for many diseases.